2008
DOI: 10.4314/eamj.v85i6.9622
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical data, anatomical site and disease stage in colorectal cancer

Abstract: Objective: to evaluate the colorectal cancer clinical data with respect to the anatomical location and stage of disease. Design: retrospective observational study. Setting: Kenyatta national Hospital (KnH), nairobi, Kenya. Subjects: Two hundred and fifty three tumours were categorised as right colonic (RCC), left colonic (lCC) and rectal (rC) lesions. the distribution of symptoms (rectal bleeding, tenesmus, change in bowel habits, abdominal pain, intestinal obstruction, rectal mass), anaemia, transfusion requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
35
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 11 publications
10
35
1
7
Order By: Relevance
“…Rectum being the most common site of occurrence of adenocarcinoma followed by sigmoid colon. These findings were in concordance with other studies by Yawe KT et al, [23] Saidi HS et al [24] and Gurjeet K et al [29] Maximum number of cases (53.7%) were observed in the age group of 60-80 years and about 30% of cases were seen in the age group of 30-50 years, exhibiting a shift in tendency of occurrence of colorectal adenocarcinoma in younger and middle aged adults. In our study the male:female ratio was found to be 1.1:1, showing almost equal incidence among both the sexes.…”
Section: Non-neoplastic Lesionssupporting
confidence: 93%
“…Rectum being the most common site of occurrence of adenocarcinoma followed by sigmoid colon. These findings were in concordance with other studies by Yawe KT et al, [23] Saidi HS et al [24] and Gurjeet K et al [29] Maximum number of cases (53.7%) were observed in the age group of 60-80 years and about 30% of cases were seen in the age group of 30-50 years, exhibiting a shift in tendency of occurrence of colorectal adenocarcinoma in younger and middle aged adults. In our study the male:female ratio was found to be 1.1:1, showing almost equal incidence among both the sexes.…”
Section: Non-neoplastic Lesionssupporting
confidence: 93%
“…[19] Bleeding is an index symptom in early stage colorectal cancer, therefore it merits an urgent and full investigation, as it is a diagnostic challenge to distinguish a benign condition from a serious underlying colorectal disease on the basis of bleeding alone. Rectal bleeding was the commonest presenting symptom for malignant lesions in the present study which is in agreement with studies of Yawe KTet al [20] and Saidi HS et al [21] Majority of the neoplastic lesions were left sided, especially involving rectum followed by recto-sigmoid and sigmoid colon, similar to the findings made by Gurjeetet al [22] There is no doubt that fibreoptic colonoscopy increases diagnostic accuracy in large bowel diseases & is especially helpful in cases where radiology is either negative or equivocal. [23] Colonoscopy and colonoscopic biopsy examinations are now performed not only for the diagnosis of diseases but also for monitoring the course of wide variety of conditions and for the early detection of complications of colonic lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Bleeding per rectum was the commonest presenting symptom which is in agreement with other findings 21,22 . It has been documented that rectal bleeding especially in older patient can be predictive of colorectal cancer especially when associated with abdominal pains or change in bowel habits 23 .…”
Section: Discussionsupporting
confidence: 92%